Compartmentalization of neuronal and peripheral serotonin synthesis in Drosophila melanogaster. - Neckameyer, W; Coleman, C; Eadie, S; Goodwin, S (2007)
In Drosophila, one enzyme (Drosophila tryptophan-phenylalanine hydroxylase, DTPHu) hydroxylates both tryptophan to yield 5-hydroxytryptophan, the first step in serotonin synthesis, and phenylalanine, to generate tyrosine. Analysis of the sequenced Drosophila genome identified an additional enzyme with extensive homology to mammalian tryptophan hydroxylase (TPH), which we have termed DTRHn. We have shown that DTRHn can hydroxylate tryptophan in vitro but displays differential activity relative to DTPHu when using tryptophan as a substrate. Recent studies in mice identified the presence of two TPH genes, Tph1 and Tph2, from distinct genetic loci. Tph1 represents the non-neuronal TPH gene, and Tph2 is expressed exclusively in the brain. In this article, we show that DTRHn is neuronal in expression and function and thus represents the Drosophila homologue of Tph2. Using a DTRHn-null mutation, we show that diminished neuronal serotonin affects locomotor, olfactory and feeding behaviors, as well as heart rate. We also show that DTPHu functions in vivo as a phenylalanine hydroxylase in addition to its role as the peripheral TPH in Drosophila, and is critical for non-neuronal developmental events.